PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN, PENGGUNAAN, DAN PENGGUNAAN E-LIQUID DI DALAM ROKOK ELEKTRIK - Annisa Tanzil K; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2018)
Smoking is one activity that is still done by individuals in all ages, from teenegers to adulthood. Many ways that can be done in the effort to stop smoking, such as commited, seplacing cigarettes by consuming candy, divert cigarettes with activity, but now smokers try to quit smoking by using electric cigarettes. Which electric cigarette is one alternative that can be done as a substitute for conventional cigarettes. Electric cigarette is a set of tools that function to convert the chemicals intp steam form, and electric cigarette consists of three(3) parts, Battery(the part contains the battery), atomizer(the part that will heat and vaporize the nicotine solution), and catridge( the part contains a nicotine solution). Electric cigarette doesn’t contain tobacco but using a liquid compound which concists of a mixture of water, nicotine, propylene glycol and flavors. According Badan Pengawasan Obat dan Makanan(BPOM) electric cigarette containing liquid nicotine, propylene glycol, diethyl glycol, and glycerin. If all of the materials is heated it wil produce nitrosamine compounds. And that compounds can cause cancer.Therefoe consumer protection must be strcly enforced.